2004
DOI: 10.1074/jbc.m311862200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CHOP Expression by Amino Acid Limitation Requires Both ATF4 Expression and ATF2 Phosphorylation

Abstract: The CHOP gene is transcriptionally induced by amino acid starvation. We have previously identified a genomic cis-acting element (amino acid response element (AARE)) involved in the transcriptional activation of the human CHOP gene by leucine starvation and shown that it binds the activating transcription factor 2 (ATF2). The present study was designed to identify other transcription factors capable of binding to the CHOP AARE and to establish their role with regard to induction of the gene by amino acid depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
217
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(231 citation statements)
references
References 43 publications
13
217
0
1
Order By: Relevance
“…Moreover, there is adequate precedent that starvation-induced translational inhibition can be associated with an increased translational yield for selected transcripts, including ATF3 and ATF4 (refs. 19,22).…”
Section: E T T E R Smentioning
confidence: 99%
“…Moreover, there is adequate precedent that starvation-induced translational inhibition can be associated with an increased translational yield for selected transcripts, including ATF3 and ATF4 (refs. 19,22).…”
Section: E T T E R Smentioning
confidence: 99%
“…To characterize ATF3 function after UV stress, knockdown experiments were performed, using a previously described siRNA (siATF3) 12 . The efficiency of this siRNA in HaCaT and HeLa cells has been shown in an earlier study.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ATF4 is overexpressed under hypoxia, 14 and that it can directly upregulate CHOP transcription through its binding to the CHOP promoter region. 5,6 Thus, we tested whether hypoxia increases ATF4 and CHOP expression in our cell lines. Both ATF4 and CHOP protein levels began to increase after 3 h in hypoxia (Figure 4a), and continuously increased for up to 12 h (experimental endpoint).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 It is a leucine-zipper transcription factor that is present at low levels under normal conditions but is highly upregulated in ER stress by ATF4. [3][4][5][6] Increased expression of CHOP promotes cell death, but the deletion of the CHOP gene leads to an attenuation in cell death induced by ER stress. 2,7 Also, the accumulation of CHOP protein during ER stress has been reported to be regulated through modulation of its degradation by the proteasome.…”
mentioning
confidence: 99%